Autologous Mesenchymal Stem Cells, Applied in a Bioabsorbable Matrix, for Treatment of Perianal Fistulas in Patients With Crohn’s Disease’ - Dietz, Allan B. (Gastroenterology, 2017)
In patients with Crohn’s disease (CD), perianal fistulas frequently recur, causing substantial morbidity. We performed a 12 patient, 6 month phase I trial to determine whether autologous mesenchymal stem cells (MSCs), applied in a bioabsorbable matrix, can heal the fistula. Fistula repair was not associated with any serious adverse events related to MSCs or plug placement. At 6 months, 10/12 patients (83%) had complete clinical healing and radiographic markers of response. We found placement of MSC-coated matrix fistula plugs in 12 patients with chronic perianal fistulas to be safe and lead to clinical healing and radiographic response in 10 patients.